Stress test reactivity in panic disorder. - Roth, W; Margraf, J; Ehlers, A; Taylor, C; Maddock, R; Davies, S; Agras, W (1992)
The psychological and physiological reactivity of 52 patients with panic disorder to mental arithmetic, cold pressor, and 5% carbon dioxide inhalation tests was compared with that of 26 age- and sex-matched normal subjects. In general, patients with panic disorder were neither more physiologically reactive to these stressors than normal subjects nor slower to recover from them, but they were tonically more anxious and much more likely to ask to stop carbon dioxide inhalation or to report panic attacks during this test. Patients who reported panic attacks (46%) had manifested greater anticipatory anxiety before the gas was delivered, accompanied with increased beta-adrenergic cardiac tone. Thus, anticipatory anxiety can be an important factor in panic provocation. Physiological measures varied greatly in their sensitivity to phasic or tonic anxiety. Carbon dioxide stimulated large increases in respiratory minute volume, but these increases were no greater for patients than for normal subjects.